2016
DOI: 10.1039/c6ra13992b
|View full text |Cite
|
Sign up to set email alerts
|

Cl2/Ar based dry etching of GaCrN using inductively coupled plasma

Abstract: Dry etching of GaCrN, a novel DMS spintronics material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The essential requirement for this is an optimized ferromagnet-GaN Schottky contact for efficient spin injection into GaN [2]. Recently, it is reported that GaCrN exhibits ferromagnetism at room temperature [3], therefore the spin injection in this material can be achieved using a ferromagnetic Schottky contact. A) Cobalt (Co) is chosen as a spin polarization material and investigate for the first time the characteristics of Co/n-GaN Schottky contact.…”
Section: Introductionmentioning
confidence: 99%
“…The essential requirement for this is an optimized ferromagnet-GaN Schottky contact for efficient spin injection into GaN [2]. Recently, it is reported that GaCrN exhibits ferromagnetism at room temperature [3], therefore the spin injection in this material can be achieved using a ferromagnetic Schottky contact. A) Cobalt (Co) is chosen as a spin polarization material and investigate for the first time the characteristics of Co/n-GaN Schottky contact.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2(a) shows the influence of RF power on the etching rate. Since RF power determines the power of the material surface bombarded by plasma, [17][18][19][20][21][22][23][24] the etching rate increases from 72 to 86 nm min −1 as the RF power increases from 100 to 300 W. As shown in Fig. 2(b), the θ decreases as the RF power increasing from 100 to 250 W. In the process of ICP etching, due to the joint action of physical and chemical etching, a beveled sidewall will naturally be formed.…”
Section: Resultsmentioning
confidence: 96%
“…The fluorine-based etch recipe used 10 sccm of SF 6 , 5 sccm of Ar, with a forward power of 100 W and a forward bias of 50 V. The chlorine-based etch recipe used 10 sccm of Cl 2 , 5 sccm of Ar, 100 W forward power, and 50 V forward bias. In both cases, there was a 10 s stabilization step, a 5 s plasma ignition step, and a constant etch lasting 5 s. These reactive chemistries were chosen due to their widespread use in the industrial etching of dielectric and ferromagnetic films, and therefore, fully understanding their impact on the Bi 2 Se 3 surface chemistry is necessary for the further application in advanced device processing. Although Bi 2 Se 3 is easily etched with inert processes, integration in novel device architectures will expose Bi 2 Se 3 to reactive sputtering processes involved in sputtering through more physically robust layers.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…However, if more robust materials are utilized in the device structure (i.e., Fe, Co, Ni, etc. ), it may be necessary to use more reactive etching processes. Therefore, the use of inductively coupled plasma (ICP) etching using Cl 2 and SF 6 reactive species was also investigated. Using angle-resolved photoemission spectroscopy (ARPES), X-ray photoelectron spectroscopy (XPS), scanning tunneling spectroscopy (STS), and atomic force microscopy (AFM), we investigate the surface chemistry, physical damage, and changes in the electronic structure induced by these destructive processes and provide a guide for minimizing and, in some cases, even reversing some of the adverse effects.…”
Section: Introductionmentioning
confidence: 99%